FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN PASIEN HEMODIALISA DI RSU HKBP BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2018 - Manurung, Melva (Universitas Prima Indonesia, 2018)
The process of hemodialysis in the hospital can cause anxiety and physical disturbing the neurological system such as weakness, fatigue, anxiety, decreased concentration. Some of the factors that affect the anxiety of hemodialysis patients are age, sex, education level, treatment experience, length of therapy, financing, family motivation. This study aims to analyze the factors that affect the anxiety level of hemodialysis patients in HKBP Balige Hospital. The design used in this study is descriptive